Clutch operating device with friction lining wear compensation analysis of properties and utilization efficiency - Riabukha, Iu. A.; Mikhalevich, N. G.; Voronova, E. M.; Yarita, A. A.; Klimenko, V. I.; Kolbasov, A. N.; Рябуха, Ю. О.; Михалевич, М. Г.; Воронова, Є. М.; Ярита, О. О.; Клименко, В. І.; Колбасов, О. М.; et al. (Харьковский национальный автомобильно-дорожный университет, 2018)
In modern conditions of competition a lot of attention is paid to the comfort of driving. Control to driveline units is no exception. Application of clutch with the system of compensation of wear of friction overlays can not only enhance comfort, due to maintaining a stable effort on the pe-dal, but also improve the performance of the clutch. In the article a comparative analysis of the traditional design of the pneumohydraulic booster (PHB) and the design, which has a mecha-nism for compensating the wear of friction plate of clutches. As a compensator for the wear of friction plate of clutches, a telescopic rod with a closed cavity is used, which is filled the brake fluid through a reverse valve. With the wear of friction clutches, the fluid has the ability to slowly flow out of the closed cavity of the rod due to the leakage of the reverse valve. A positive feature is the ability to implement the proposed design within the framework of the traditional design of the pneumatic booster without changing the basic parts. As a result of the application of the proposed designs, it is expected to obtain such positive qualities as reducing the mass and mate-rial capacity of the product, maintaining high clutch performance regardless of the degree of wear of friction plates, reducing air consumption in operation (and, consequently, reducing fuel consumption), reducing the overall dimensions of the PHB. In order to confirm the new quali-ties, the consumption of air and fuel during the operation of both design of PHB on the typical urban route in the route bus is calculated. When calculating, the clutch exclusions taken into account are required during acceleration after each stop and traffic light. A reference to the investigation of the speed of the clutch control mechanism with new and worn friction plate of clutch is given. The properties of the proposed PHB design with the mechanism of compensation of the wear of the friction plate of the clutch are analyzed and the effect is shown not only in the manufacture of this design, but also from the application of this design in operation, which is expressed in fuel economy.
Механізм керування зчепленням з компенсацією зносу фрикційних накладок. Аналіз властивостей і ефективності використання
Механизм управления сцеплением с компенсацией износа фрикционных накладок. Анализ свойств и эффективности использования
Keywords: pneumohydraulic booster; compensation mechanism for friction linings wear; fuel economy; reduction of compressed air consumption; ПГУ; зменшення металоємності; механізм компенсації зносу фрикційних накладок; економія палива; зменшення споживання стисненого повітря; ПГУ; уменьшение металлоёмкости; механизм компенсации износа фрикционных накладок; экономия топлива; уменьшение потребления сжатого воздуха; 681.583.35